Urbanisasi di Malaysia: mengaitkan kepelbagaian proses ke bentuk perbandaran - Abdul Samad Hadi, (Environmental Management Society, Malaysia, 2010)
The essence of the Seminar on Ecology, Human Habitat and Environment is the dynamic relations between man and the environment. The outcomes of the relation are shown on the human habitat. This plenary paper discusses the relation stated earlier focusing on the argument that changing drivers from a situation of linearity to a complex one, has brought changing impacts on the human habitat. These changes can be illustrated from the Malaysian urbanization experiences that have undergone through three major phases, namely the nascent, pseudo and the current extended mega-urban region. The nature of development drivers at each phase, a simple one in the first phase, increasingly diversify in the second phase to the more diversified and complex drivers show the increasingly complex changes. The role of the market has penetrated the man and environment relations to produce a complex human habitat that has to be made liveable, for the welfare of all people